The relationship between socio-demographics and financial literacy with financial planning among young adults in Klang Valley, Malaysia - Yong, Kah Chun; Chung, Jee Fenn; Akram Abdulraqeb Sultan Al-Khaled (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to explore the relationship between socio-demographics and financial literacy with an individual’s engagement in personal financial planning, with the target population being the youths residing in Klang Valley, Malaysia. Questionnaires adopted from past literature were distributed to gather relevant data from the target population and 400 respondents participated in this study in total. The results show that age, education level, income level and financial literacy have relationships with personal financial planning, while gender does not. The limitations of this study include the omission of other variables such as behavioral, environmental, and psychological factors that may affect financial planning, as well as geographical constraints whereby other states and federal territories with varying state of development, cost of living and lifestyle may need to be considered to present a more comprehensive research framework and provide more accurate findings. Lastly, this research serves as a guide to the relevant authorities in reviewing the sufficiency and effectiveness of financial education currently in place in the country.